(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2016)
In today’s global market, a major challenge for every economic entity is to be competitive and achieve its objectives. The method of survival shows that those companies with the lowest costs will survive and remain on the market. G. J. Stigler explained this technique on the market share of different sized companies in the steel industry in the United States. In his method he groups enterprises by size (small, medium and large). Historically, it is known that economic entities have been joining together since the Middle Ages. At that time, traders who formed associations were not engaged only in trade, but also in transportation and monetary activity. Economic entities are still joining together today, mostly in the form of a cooperative, cluster, cooperation, public private partnership or holding. The reason for that lies in the reduction of costs, risks and competition and the possibility of increasing the capacity of economic entities. Also, it should be noted that there is a synergy effect when economic entities join together. We are witnesses of many failed businesses, which did not respond to the economic crisis and the needs of the market. The aim of this paper is to try to connect the technique of survival and joining of economic entities and show how a merger is one of the survival models that in conditions of economic crisis provides options to business entities. Only companies with the lowest costs and high-quality technology can survive and compete in today’s market. Keywords: Survival techniques, joining businesses, cooperatives, market share